Pengaruh Profitabilitas Struktur Modal Dan Keputusan Investasi Terhadap Nilai Perusahaan Pada Perusahaan Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Dhea Oktavia Pratiwi; Nasrul Kahfi Lubis; Muhammad Salman (LPPM Universitas Labuhanbatu, 2022)
This study aims to determine the effect of profitability, capital structure and profitability on firm value in food and beverage sector companies listed on the Indonesian stock exchange for the period 2011-2021. This type of research is quantitative. The research population is all companies that are members of food and beverage companies listed on the Indonesia Stock Exchange. The research sample was determined based on the sample selection technique, namely purposive sampling as many as 13 data from food and beverage companies. The data analysis method used is the classical assumption test such as normality test, heteroscedasticity test and autocorrelation test and hypothesis testing such as multiple linear regression test, t test, f test, and R2 test using SPSS as an analytical tool. Results. The multiple linear regression equation is Y = -3.326 + 22.854 X1 + 1.086 X2 + 0.175 X3. With a Fsign value of 0.0000 <0.05, it means that partially or simultaneously the profitability of capital structure and investment decisions have an effect on firm value. This simple study only uses three independent variables and is only proxied by one measurement on each variable.